Nucleus Accumbens Shell and mPFC but Not Insula Orexin-1 Receptors Promote Excessive Alcohol Drinking - Lei, Kelly; Wegner, Scott A.; Yu, Ji Hwan; Mototake, Arisa; Hu, Bing; Hopf, Frederic W. (Frontiers in Neuroscience, 2016)
Addiction to alcohol remains a major social and economic problem, in part because of the high motivation for alcohol that humans exhibit and the hazardous binge intake this promotes. Orexin-1-type receptors (OX1Rs) promote reward intake under conditions of strong drives for reward, including excessive alcohol intake. While systemic modulation of OX1Rs can alter alcohol drinking, the brain regions that mediate this OX1R enhancement of excessive drinking remain unknown. Given the importance of the nucleus accumbens (NAc) and anterior insular cortex (aINS) in driving many addictive behaviors, including OX1Rs within these regions, we examined the importance of OX1Rs in these regions on excessive alcohol drinking in C57BL/6 mice during limited-access alcohol drinking in the dark cycle. Inhibition of OX1Rs with the widely used SB-334867 within the medial NAc Shell (mNAsh) significantly reduced drinking of alcohol, with no effect on saccharin intake, and no effect on alcohol consumption when infused above the mNAsh. In contrast, intra-mNAsh infusion of the orexin-2 receptor TCS-OX2-29 had no impact on alcohol drinking. In addition, OX1R inhibition within the aINS had no effect on excessive drinking, which was surprising given the importance of aINS-NAc circuits in promoting alcohol consumption and the role for aINS OX1Rs in driving nicotine intake. However, OX1R inhibition within the mPFC did reduce alcohol drinking, indicating cortical OXR involvement in promoting intake. Also, in support of the critical role for mNAsh OX1Rs, SB within the mNAsh also significantly reduced operant alcohol self-administration in rats. Finally, orexin ex vivo enhanced firing in mNAsh neurons from alcohol-drinking mice, with no effect on evoked EPSCs or input resistance; a similar orexin increase in firing without a change in input resistance was observed in alcohol-naïve mice. Taken together, our results strongly suggest that OX1Rs within the mNAsh, but not the aINS, play a central role in driving excessive alcohol drinking.